Pengaruh Atribut Produk Terhadap Keputusan Pembelian Kopi Robusta - Hoeriah, Siti; Hidayati, Reny; Jakiyah, Ulpah (Cangkok, 2023)
Robusta (coffea canephora) coffea becomes one of the favored commodities and is the most widely cultivated in Indonesia the purpose of this study is for (1) to discover how attributes of the product are affectted of the decision to buy robusta coffe at tasikmalaya city”s kahaji coffe shop and (2) to know which variables of the quality of the product have the most influence on the decision to buy robusta coffe at the kahaji coffe shop Tasikmalaya city. This study use the survey method or research and data collection using methods, interviews, observation and questionnaires. Up to the study of 95 respondents and was a consumer who made visits or bought coffe at the kahaji cafe, using technique samples Accidental Sampling and analysis models are using linear regression. Result in this study explain that (1) the attributes of the kahaji coffe products are both partial and simultaneously have an effect significant attribute variable on the purchase decision of kahaji coffe is the aroma variable and the price because it has a smaller value than 0,05’s 0,000.